The Genre of Still Life in Contemporary Painting of St. Petersburg Artists-Academicians - Gracheva, Svetlana M. (Actual Problems of Theory and History of Art, 2018)
Fine art in Russia now enters a new phase, associated with the changes in the entire socio-cultural situation, with the impact of new technologies on culture, and with the development of the art market, which, as it turned out, was not a panacea for the pressing problems of society. On the background of general changes in the field of artistic culture, when the principle of representation of author’s works changes and an artifact gains the largest value and kind of an art brand created on behalf of the artist, certain metamorphosis of fine art causes it to lose its familiar form and criteria. Such sustainable concepts as “school”, “professionalism”, “expertise” do change.It is interesting to see in such a genre as still life, strongly connected with the objective world, the notion of an art object and an artifact, the development of modern academic art. Still life is as important both as a “school” stage in the formation of professional level of an artist and as an independent genre of fine art with its rich history and specific way of world perception and even as a style-forming factor in art.Still life “dead”, “frozen” nature conveys an artist’s world in its subject, material, aspect, reveals the understanding of the world through material medium. In still life the interpretation of space is different than, for example, in the landscape: the objects and not the natural environment play the major role. Of course, still life can be solved as landscape and vice versa, because there is some principle, worldview in it. Modern still life and other genres often trespass the usual boundaries. Still life as a genre is becoming one of the most popular in the works of contemporary artists-academics.In the art of St. Petersburg masters, this genre is developing in several directions. The first direction, classical one, is represented by works of such masters as A. K. Bystrov, A. N. Bliok, and V. V. Zagonek. The painting of K. V. Grachev presents it as a philosophical genre and built on the achievements of the so-called “spherical perspective”. V. A. Mylnikova created still lifes of decorative direction. Expressionistic tendencies, based on the picturesque expressionism, are manifested in painting of S. D. Kichko, Yu. V. Kaluta, D. A. Collegova. Still life, emblematic in its original meaning as a genre that rests on deep symbolic subtext, took place in painting of such artists as N. Ryzhikova, E. Bazanova, O. Shwiderskaya. All these artists produce still life paintings both as independent works of art and parts of subject compositions. The study of evolution and the specifics of the genre of still life in contemporary St. Petersburg academic art would help to gain deeper understanding of indigenous processes taking place in Russian art as a whole.
Keywords: still life; genre; contemporary art; St. Petersburg painting; academic art; the world of objects; expressionist trends; monumental; philosophical genre